Uniportal VATS live surgery around the world - Office, Editorial (Video-Assisted Thoracic Surgery; Vol 1 (August 2016): Video-Assisted Thoracic Surgery, 2016)
Prof. Diego Gonzalez-Rivas is launching a uniportal ‘transformation’ worldwide. So far, he has been invited to a huge number of countries and cities for live surgery demonstration, bringing the technique to a fast increasing number of thoracic surgeons. Dr. Gonzalez Rivas is probably the surgeon in the history of surgery, not just thoracic surgery, who has operated patients in more number of hospitals and countries around the world. With its wider application, uniportal VATS will benefit more and more patients. This effort of constant travelling, performing masterclasses and live surgery onsite, from the east to the west of the world, represents a new revolutionary way of learning. Teaching and sharing experiences in every country allows the increase and quicker worldwide adoption of the technique during the last years.